Anterior longitudinal ligament in diffuse idiopathic skeletal hyperostosis: Ossified or displaced?. Issue 9 (24th May 2018) - Kuperus, Jonneke S.; Smit, Esther J. M.; Pouran, Behdad; van Hamersvelt, Robbert W.; van Stralen, Marijn; Seevinck, Peter R.; Buckens, Constantinus F.; Bleys, Ronald L. A. W.; Weinans, Harrie H.; Oner, F. Cumhur; de Jong, Pim A.; Verlaan, Jorrit‐Jan
ABSTRACT: Diffuse idiopathic skeletal hyperostosis (DISH) is often theorized to be an ossification of the anterior longitudinal ligament (ALL). Using computed tomography (CT) imaging and cryomacrotome sectioning, we investigated the spatial relationship between the ALL and newly formed bone in DISH to test this hypothesis. In the current study, four human cadaveric spines diagnosed with DISH using CT imaging were frozen and sectioned using a cryomacrotome. Photographs were obtained of the specimen at 125 µm intervals. Manual segmentations of the ALL on cryomacrotome photographs were projected onto the three‐dimensional reconstructed CT scans. The presence and location of newly formed bone were assessed in relationship to the location of the ALL. The ALL could be identified and segmented on the photographs at all levels. The ALL was located at the midline at levels where no new bone had formed. At the locations where new bone had abundantly formed, the ALL was displaced towards to the contralateral side and not replaced by bony tissue. The displacement of the—morphologically normal appearing—ALL away from the newly formed bone implies that newly formed bone in DISH may not originate from the ALL. © 2018 The Authors. Journal of Orthopaedic Research ® Published by Wiley Periodicals, Inc. on behalf of Orthopaedic Research Society J Orthop Res 36:2491–2496, 2018.